Clinical performance of glass ionomer cement and composite resin in Class II restorations in primary teeth: A systematic review and meta-analysis - Dias, Ana Giselle Aguiar [UNESP]; Magno, Marcela Baraúna; Delbem, Alberto Carlos Botazzo [UNESP]; Cunha, Robson Frederico [UNESP]; Maia, Lucianne Cople; Pessan, Juliano Pelim [UNESP] (Elsevier, 2018)
Objectives: This study compared the clinical performance of glass ionomer cement (GIC) compared to composite resin (CR) in Class II restorations in primary teeth. Data: Literature search according to PRISMA guidelines including randomized controlled trials comparing Class II restorations performed with GIC, compared to CR, in primary teeth. Sources: PubMeb, Scopus, Web of Science, VHL, Cochrane Library, Clinical Trials and OpenGrey, regardless of date or language. Study: Ten studies were included in qualitative synthesis, and 9 in the meta-analyses (MA). Six studies were classified as low risk of bias, and 4 as “unclear”. Heterogeneity ranged from null to high (0% to 73%). GIC and CR presented similar failure patterns (risk difference −0.04 [−0.11, 0.03]; p = 0.25, I2 = 51%), and the exclusion of studies with follow-up period <24 months, or grouping according to the type of GIC (conventional or resin-modified), or according to the type of isolation (cotton roll or rubber dam), or according to the evaluation criteria applied did not affect the pattern of the results obtained. GIC exhibited significantly lower values of secondary carious lesions (SCL) than CR (SCL: risk difference 0.06 [0.02, 0.10], p = 0.008, I2 = 0%). The materials presented similar performance (p > 0.05) regarding the overall effect, as well as for marginal discoloration, marginal adaptation and anatomical form. The superiority of GIC was maintained when resin-modified GIC and rubber dam isolation were analyzed separately. Conclusions: GIC and CR presented similar clinical performance for all criteria analyzed, except for secondary carious lesions, in which GIC presented superior performance, especially for the resin-modified GIC and with rubber dam isolation.
Keywords: Child; Composite resin; Glass ionomer cement; Primary teeth